Evolution of life cycle dimorphism: An example of sacoglossan sea slugs. (21st September 2021) - Yamaguchi, Sachi; Yusa, Yoichi; Iwasa, Yoh
Highlights: In simple life cycle, mothers produce benthic offspring by direct development. In complex life cycle, mothers produce planktotrophic larvae which become benthos. Life cycle dimorphism is not common among marine species except some sea slugs. We studied the condition for different life cycle types to coexist mathematically. The condition holds if benthos experience strong density dependence in summer. Abstract: Many sea slugs of Sacoglossa (Mollusca: Heterobranchia) are sometimes called "solar-powered sea slugs" because they keep chloroplasts obtained from their food algae and receive photosynthetic products (termed kleptoplasty). Some species show life cycle dimorphism, in which a single species has some individuals with a complex life cycle (the mother produces planktotrophic larvae, which later settle in the adult habitat) and others with a simple life cycle (mothers produce benthic offspring by direct development or short-term nonfeeding larvae in which feeding planktonic stages are skipped). Life cycle dimorphism is not common among marine species. In this paper, we ask whether some aspects of the ecology of solar-powered sea slugs have promoted the evolution of life cycle dimorphism in them. We study the population dynamics of the two life-cycle types that differ in summer (one with planktonic life and the other with benthic life), but both have benthic life in other seasons. We obtain the conditions in which two types with different life cycles coexist stably or a single type generating offspring with different life cycles evolves. We conclude that the stable coexistence of two life cycles can evolve if benthic individuals in summer experience strongly density-dependent processes or if the between-year fluctuation of biomass growth in summer is very large. We discuss whether these results match the life cycles of solar-powered sea slugs with life cycle dimorphism.